Referential equivalence between the English and Vietnamese versions of "Lolita". - Pham, Thi Hong Nhung (ĐHNN, 2017)
In today‘s world where no nation can ignore the globalization trend, the demand for easy access to the body of literary works of a country is greater than ever before. More and more literary works are being translated from English, the international language of communication into Vietnamese, for various purposes. This calls for academic studies into the field of literary translation. It is extremely necessary to evaluate the quality of the translation text with a view to improving translation in general and Literary Translation in particular. This study aims at revealing the most basic features of English literary text and basic concepts of translation theory in general, literary translation in particular. Then it will test the appropriateness of House‘s mode l for translation quality assessment in assessing Vietnamese version of English novel ―Lolita‖ regarding referential equivalence. Finally, suggestions for further studies in translating English literary texts into Vietnamese will be proposed.